2013
DOI: 10.1111/boc.201200088
|View full text |Cite
|
Sign up to set email alerts
|

MED1101: A new dialdehydic compound regulating P2×7 receptor cell surface expression in U937 cells

Abstract: Our results clearly demonstrate that in U937 monocyte cells MED1101 acts as a P2×7R antagonist through the induction of receptor internalisation and subsequent inhibition of down-stream signal transduction pathways that regulate monocyte migration/transmigration, thus playing a potential therapeutic role in inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…Other compounds may also be of value in modulating P2X7 expression. Recently, the dialdehydic compound 2-[1-(6-amminopurin-9-il)-2-osso-etossi]prop-2-enale (MED1011) was developed and shown to downregulate the expression and function of P2X7 in macrophages by causing the internalization of P2X7 in these cells (Muzzachi et al, 2013). Moreover, the medicinal extract from Aloe vera has been shown to downregulate P2X7 expression in macrophages to attenuate IL-1b secretion (Budai et al, 2013).…”
Section: Modulators Of P2x7 Receptor Expressionmentioning
confidence: 99%
“…Other compounds may also be of value in modulating P2X7 expression. Recently, the dialdehydic compound 2-[1-(6-amminopurin-9-il)-2-osso-etossi]prop-2-enale (MED1011) was developed and shown to downregulate the expression and function of P2X7 in macrophages by causing the internalization of P2X7 in these cells (Muzzachi et al, 2013). Moreover, the medicinal extract from Aloe vera has been shown to downregulate P2X7 expression in macrophages to attenuate IL-1b secretion (Budai et al, 2013).…”
Section: Modulators Of P2x7 Receptor Expressionmentioning
confidence: 99%
“…Pannexin-1 has been implicated as the protein associated with the P2X7R pore [ 30 , 36 ]. For this reason, we examined whether our methodology was specific for P2X7R pore activity.…”
Section: Resultsmentioning
confidence: 99%
“…The J774.G8 macrophage cell line, which was previously demonstrated by us to natively express P2X7R and the Pannexin-1 channel [ 10 ], as well as other P2 subtypes, including P2X4R and P2Y1, P2Y2 and P2Y4 receptors [ 29 ]. And U937 human monocyte cell line [ 30 , 31 ], were routinely maintained in RPMI 1640 medium supplemented with 10% fetal bovine serum at 37°C under an atmosphere containing 5% CO 2 . Every three days, the medium was changed, and the cells were adjusted to a density of 4x10 6 cells per 150 cm 2 cell culture flask (Corning).…”
Section: Methodsmentioning
confidence: 99%
“…Many of studies have indicated that activation of P2X7 receptors can promote migration in different types of cells, such as monocytes [26], tumor cells [27], and epithelial cells [28]. P2X7 receptors have also been shown to promote the migration of cultured glial cells [29].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…P2X7 receptors have also been shown to promote the migration of cultured glial cells [29]. Moreover, P2X7 receptor activation was demonstrated to trigger extracellular calcium ion influx, then activate intracellular kinases, such as MAPK [26,28] and Akt [30], or increase the expression of matrix metalloproteinase 9 [29], thereby facilitating cell migration. Moreover, Fyn kinase, one member of the Src family, is involved in OPC migration [31,32].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%